Transient neonatal hyperthyrotropinemia: prevalence and its associated materno-fetal factors: a hospital based prospective observational study - Karnam, Padmini S.; Sathiyamoorthi, Sathiyanarayanan (International Journal of Contemporary Pediatrics, 2025)
Background: Transient neonatal hyperthyrotropinemia (TNH) should be interpreted with caution in newborns, to assess the risk of unnecessary treatment. There are very few studies reporting prevalence of TNH which ranges from 0.02 to 6.0%. Hence, this study was conducted to estimate the prevalence of TNH among neonates and factors associated with it. Methods: A prospective observational study was conducted among neonates born for a period of one year. All neonates were subjected to thyroid hormones screening on day 3-5, and if TSH level was elevated (10-20 mIU/l), a repeat TSH and T4 after 2 weeks were done. Elevated TSH levels at 3-5 days with normal T4 levels, normalizing on re-examination at 2-4 weeks was diagnosed as TNH. Descriptive data were reported as frequencies. Chi square and unpaired ‘t’ test was used to study association. Odd’s ratio was calculated to study the strength of association using regression analysis. Results: Out of 333 neonates studied, 17 (5.1%) had elevated TSH levels with normal fT4 on initial screening. Of 15 newborns who returned for follow up at 2 weeks, 14 (4.1%) neonates returned to normalcy, indicating the prevalence of TNH as 4.1%. Prevalence of TNH among neonates born to hypothyroid mothers (45) was 11.1%. Maternal hypothyroid status, birth weight, head circumference and gestational age were statistically significant with TNH. Conclusions: Screening of all newborns for congenital hypothyroidism (CH) is useful, as they benefit from early initiation of treatment. However, interpretation of thyroid hormones must be done with utmost caution.